Preliminary assessment of the feasibility of using AB words to assess candidacy in adults - Vickers, Deborah A.; Riley, Alison; Ricaud, Rebecca; Verschuur, Carl; Cooper, Stacey; Nunn, Terry; Webb, Kath; Muff, Joanne; Harris, Frances; Chung, Mark; Humphries, Jane; Langshaw, Alison; et al. (Taylor & Francis, 2016)
Background: Adult cochlear implant (CI) candidacy is assessed in part by the use of speech perception measures. In the United Kingdom the current cut-off point to fall within the CI candidacy range is a score of less than 50% on the BKB sentences presented in quiet (presented at 70 dBSPL).